Ferric metformin drug complex supported on magnetic nanofiber cellulose; An efficient access to 4-H pyrans derivatives and determination of their antimicrobial activity. Issue 7 (3rd April 2022) - Matloubi Moghaddam, Firouz; Daneshfar, Maryam; Moghimi, Hamid; Daneshfar, Zahra
Abstract: Magnetic nanofiber cellulose (NFC) was selected as a biopolymer surface for the reaction with ferric metformin and a novel nanocatalyst was prepared. This green heterogeneous organometallic catalyst was analyzed by physiochemical techniques. The new metformin drug complex supported on magnetic NFC was used as a powerful and efficient catalyst for the synthesis of functionalized 4H-pyrans derivatives. The antimicrobial activity of the products showed excellent activity against all the bacterial and fungal strains (especially compounds 7q and 6r ). Graphical Abstract: UF0001